IMPLEMENTATION OF MERDEKA CURRICULUM HISTORY LEARNING AT THE HIGH SCHOOL LEVEL (COMPARATIVE STUDY IN SEVERAL HIGH SCHOOLS IN THE CITY OF JAKARTA): Implementasi Pembelajaran Sejarah Kurikulum Merdeka di Tingkat SMA (Studi Banding di Beberapa SMA di Kota Jakarta) - Yusuf Budi Prasetya Santosa; Ponco Setiyonugroho; Hendi Irawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
In the Merdeka Curriculum there are changes in substance in subjects at the upper secondary level. One of the subjects that has changed is the subject of history. The history subjects in the Merdeka Curriculum were again merged into Indonesian history subjects, which were previously Indonesian history subjects for compulsory groups and specialization groups. This study uses a descriptive qualitative methodology, with the aim of seeing how the implementation of history learning in the Independent Curriculum at the senior secondary level, and knowing the inhibiting factors in its implementation. The results of the study found that there were still history teachers who did not understand the concept and implementation of history learning in the Independent Curriculum; The Merdeka Curriculum is considered more practical and flexible compared to the 2013 Curriculum; and the lack of outreach and training in the Independent Curriculum for history teachers.